A revision of the species of the subfamily Habrocerinae of the world. Supplement I. (Coleoptera: Staphylinidae). - Assing, Volker; Wunderle, Paul (Contributions to Entomology = Beiträge zur Entomologie, 1996)
Further data on the distribution of several species of Habrocerus Erichson are presented, among them first records of H. cyprensis Assing & Wunderle from Rodhos (Greece) and of H. indicus Assing & Wunderle from Nepal. Two new species of Habrocerinae, Habrocerus schuelkei sp. n. from China and Nomimocerus conus sp. n. from Chile, are described and compared with the related Habrocerus schwarzi Horn, H. tichomirovae (Filatova) and Nomimocerus parvispinosus Assing & Wunderle, respectively. The primary and secondary male sexual characters are figured. Keywords Coleoptera, Staphylinidae, Habrocerinae, Habrocerus, Nomimocerus, world, taxonomy, revision, new species, distribution. Nomenclatural Acts schuelkei Assing & Wunderle, 1996 (Habrocerus), spec. n. conus Assing & Wunderle, 1996 (Nomimocerus), spec. n.